Should we recommend universal neonatal hearing screens?. Issue 12 (December 2015) - Shanmukanathan, Thulasi; Rodgers, David
Abstract : Evidence‐Based Answer : Yes. Universal neonatal hearing screens (UNHS) lead to earlier referral of infants with hearing impairment, resulting in a beneficial effect on language skills (SOR: B, multiple systematic reviews consisting of large numbers of low‐quality studies).